2020
DOI: 10.3390/medicines7030013
|View full text |Cite
|
Sign up to set email alerts
|

High Serum Phosphate Level as a Risk Factor to Determine Renal Prognosis in Autosomal Dominant Polycystic Kidney Disease: A Retrospective Study

Abstract: Background: Serum phosphate levels, which are associated with the progression of renal dysfunction in chronic kidney disease, in patients with autosomal dominant polycystic kidney disease (ADPKD) are lower than those in patients with other kidney diseases. However, their role in ADPKD remains unclear. This study aimed to determine whether serum phosphate levels could have an association with renal prognoses among patients with ADPKD. Methods: In total, 55 patients with PKD1 or PKD2 mutations but not undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The current results agree with previous research showing anaemia as an indicator for worse CKD outcomes [ 42 ]. The inverse association between kidney failure and haemoglobin levels was also observed in non-diabetic CKD and autosomal dominant polycystic kidney disease G2-G5 CKD patients [ 43 , 44 ]. Erythropoiesis-stimulating agents slowed progressive CKD in a non-dialysis dependent population [ 45 ].…”
Section: Discussionmentioning
confidence: 96%
“…The current results agree with previous research showing anaemia as an indicator for worse CKD outcomes [ 42 ]. The inverse association between kidney failure and haemoglobin levels was also observed in non-diabetic CKD and autosomal dominant polycystic kidney disease G2-G5 CKD patients [ 43 , 44 ]. Erythropoiesis-stimulating agents slowed progressive CKD in a non-dialysis dependent population [ 45 ].…”
Section: Discussionmentioning
confidence: 96%
“…Phosphate levels have been shown to affect patient prognoses within a range of studies [ 25 , 26 , 27 , 28 ]. Similar to prior research, our study also revealed that phosphate levels are an important factor that influenced hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Before devising personalized medicine approaches in patients with CKD, high-quality databases must be created and risk factors for the acceleration of the CKD progression must be identified (113,115,118,119,(124)(125)(126)(127)(128)(129), paying attention to attributes such as sex differences or ages (130,131). Indeed, it has been reported that even data used in AI should be divided according to sex and attribute, which makes collecting data disaggregated by age and sex essential if AI is to fulfill its promise of improving outcomes for everyone (132)(133)(134)(135).…”
Section: Attribute-based Medicine For Patients With Obesity and Ckdmentioning
confidence: 99%